Healthcare professionals knowledge of inherited cardiac arrhythmias ica their views towards and confidence in caring for a person with an ica in a surgical environment. (3rd October 2022) - McGlinchey, L; Barr, O; Black, P
Abstract: Background: Inherited Cardiac Arrhythmias (ICA) are potentially life-threatening conditions which may be induced by several factors during the perioperative period. Safety and quality of care of patients may be affected by insufficient knowledge, or confidence by healthcare professionals in surgical areas. Purpose: To determine the knowledge of ICAs by healthcare professionals, their views towards and confidence in caring for a person with an ICA in a surgical environment. Methods: In Phase One, a twenty-four item questionnaire was distributed to registered nurses and midwives, surgeons and anaesthestists within surgical areas of seventeen hospitals of the Republic of Ireland and Northern Ireland. Results: Completed questionnaires were returned from 154 participants in Phase 1 involving all four professions of the participant cohort. This comprised of one hundred and seventeen nurses, seven midwives, ten surgeons and nineteen anaesthetists. Sudden Adult/Arrhythmic Death syndrome (SADs) was heard of by 91% of participants, and 54% have heard of ICA. The majority of participants were not at all confident or only slightly confident (48% and 32%) in caring for patients with an ICA. Eighty-four percent were not aware (61.7%) or not sure if they were aware (22.7%) of the drugs to avoid in ICA conditions such as Long QT and Brugada syndrome. Those aware (11%) of drugs to avoid were seven anaethetists, two midwives and eight nurses. Of the ten surgeons, none were aware of the drugs to avoid. When all participants were asked how relevant is knowledge of ICA to your current role 5.8% said it was not at all relevant, 29.2% said it was slightly relevant, 31.8% moderately relevant and 28.6% extremely relevant. Ninety-five percent (95%) of participants would like further education about these conditions delivered mainly by online sessions and face to face workshop methods. Conclusions: There is limited knowledge of and confidence in caring for people with Inherited Cardiac Arrhythmias in surgical areas of the hospitals surveyed. Education is required in relation to awareness and identification of people with these conditions, signs and symptoms, unmasking and triggering a cardiac event and what medications need to be avoided. Patients may not be aware they have an Inherited Cardiac Arrhythmia, so healthcare professionals' awareness is crucial with the ability to recognise and respond appropriately to a possible cardiac event. There is a need to address these gaps as these have potential serious implications for people with an ICA during their perioperative journey. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The Cormac Trust